2003
DOI: 10.1152/ajpregu.00331.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol alters carbonic anhydrase-mediated renal sulfate secretion

Abstract: Active transepithelial sulfate secretion rate by winter flounder renal proximal tubule epithelium in primary culture (fPTC) is dependent on intracellular carbonic anhydrase (CA) and enhanced by cortisol. To further evaluate this relationship, a partial cDNA clone (327 bp) of carbonic anhydrase II (CAII) with high sequence similarity to CAII from numerous species including fish, chicken, and human was obtained from fPTCs. The majority of CA activity and CAII protein was present in the cytosol of fPTCs; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
(63 reference statements)
2
12
0
Order By: Relevance
“…Renal tubular CA activity is elevated 78% in rabbits undergoing metabolic acidosis, and increased renal acid excretion accompanies the induction of CA activity (14). As noted above, small changes in CA activity induced by cortisol alter the CA-dependent fraction of tubular SO 4 2Ϫ secretion (61). If…”
Section: Is Therementioning
confidence: 93%
See 2 more Smart Citations
“…Renal tubular CA activity is elevated 78% in rabbits undergoing metabolic acidosis, and increased renal acid excretion accompanies the induction of CA activity (14). As noted above, small changes in CA activity induced by cortisol alter the CA-dependent fraction of tubular SO 4 2Ϫ secretion (61). If…”
Section: Is Therementioning
confidence: 93%
“…A portion of CAII (329 bp) was recently cloned from the winter flounder proximal tubule, and CAII protein was shown to be both cytosolic and membrane associated (61). Furthermore, CAII protein migrated differently than purified bovine 4.…”
Section: Paired T-test)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, until the finding of CA-mediated SO 4 2-excretion (Renfro et al, 1999), it was believed that the kidney of marine fish lacked CA activity entirely. Although relatively few species have been examined, the available data derived from studies using isolated tubules or employing immunocytochemistry suggest that CA is present in the kidneys of both marine and freshwater fish (Renfro et al, 1999;Pelis et al, 2003;Pelis and Renfro, 2004;Georgalis et al, 2006a;Gilmour et al, 2007a). The predominant CA isoform in trout kidney is the general cytosolic variant (tCAc) (Esbaugh et al, 2005).…”
Section: Ca In Renal Acid-base Regulationmentioning
confidence: 99%
“…Although previous studies have reported the presence of 'CA II' in fish kidney [e.g. Osorezan dace (Hirata et al, 2003); winter flounder (Pleuronectes americanus) (Pelis et al, 2003)], this renal CA is probably more appropriately termed cytosolic CA ('c' or 'a' nomenclature; see above). In trout and flounder, cytosolic CA is found within proximal tubules where it immunolocalizes to the cytosol and brush border membranes (Pelis and Renfro, 2004;Georgalis et al, 2006a) (Fig.…”
Section: Ca In Renal Acid-base Regulationmentioning
confidence: 99%